Meningkatkan Speed Hauler OB Dengan Optimasi Material Piroklastik - Bardan Rajabi; Bondan Kesowo; Muhammad Piqri Ardiansyah; Kartiko Seto Aji (CV. Green Publisher Indonesia, 2026)
One of the biggest challenges facing YTD production volume in the first quarter was hauler unit productivity, particularly its speed. This significantly impacted the Engineering Department's Key Performance Indicators (KPIs) and significantly hampered jobsite performance. This issue also resulted in slow roll-off times and accelerated tire life on haulers. Therefore, this issue garnered serious attention from the engineering department, which collaborated and synergized with the production department. This vision was realized through the formation of an improvement team to improve road repairs, positively impacting speed, roll-off times, and tire life. The improvement results obtained by the NITROUSPEED team included increasing the OB Hauler speed from 18.32 km/h to 21 km/h by optimizing pyroclastic material at Pit 2 of PT. Putra Perkasa Abadi Bukit Asam site Period May - August 2024 so that it increases the profits that can be obtained with the improvements that have been made to slow down the speed of the OB hauler, namely reaching IDR 16,999,817,898,- in the period January to April 2024.